Modernism on the Punch Tape: Editing the 1984 Ulysses. Issue 1 (February 2020) - Crowley, Ronan; Schäuble, Joshua
Abstract : This article explores the set of interlocking and overlapping institutional, pedagogical, and commercial developments that led to the critical editing of James Joyce's Ulysses by Hans Walter Gabler in the late 1970s and early 1980s. While the polarised reception of Ulysses: A Critical and Synoptic Edition in the late 1980s is well known, we reconstruct the material and technological conditions of digital scholarly editing that gave rise to this major edition of a canonical modernist work.